If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + c + 6 = 0 Reorder the terms: 3 + 6 + c = 0 Combine like terms: 3 + 6 = 9 9 + c = 0 Solving 9 + c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + c = 0 + -9 Combine like terms: 9 + -9 = 0 0 + c = 0 + -9 c = 0 + -9 Combine like terms: 0 + -9 = -9 c = -9 Simplifying c = -9
| 9+4x=3(x+4) | | 4-6m=(3m+14)-2(3m+5) | | 1.2t+3.4=-1.0 | | 6y+14=-7-y | | 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x |